Formação permanente: a profissionalidade docente, um percurso formativo - Jangrossi, Rosemeire Gomes dos Santos (2020)
This dissertation presents the analysis on Ongoing Formation, Teaching Professionality in a Formative Course, evidencing the importance of the permanent personal and school formative trajectory, for the continuous constitution of efficient, successful and current teaching professionalism. The research investigated the training path of a group of five teachers from the Civil Society Organization IJ SI, located in the municipality of São Bernardo do Campo / SP, which provides daycare for children aged 01 to 03 years, in the one-year term. In the investigation, the objective was to understand the process of permanent training promoted in the school environment and its articulation with pedagogical praxis, analyzing how teachers interact with their own professional development, as well as understanding how the actions carried out on this path give meaning and boost the development of their teaching professionality. The qualitative approach was adopted, using information collection procedures and instruments, such as: documentary research, participant observation and questionnaire. The theoretical framework was constituted in the study of the authors: Francisco Imbernón, Paulo Freire, Marcelo Garcia, Marina Feldmann, Maurice Tardif, Neide Noffs, José Gimeno Sacristan and Marcos Masetto. It was intended not only to make a description of the information collected, but to contribute to the discussions about ongoing training, through analysis of the information collected, connections and relationships that led to explanations and interpretations in the production of knowledge about the relevance of ongoing training and the development of teaching professionalism